Prevalence and risk factors of gestational diabetes mellitus among pregnant women in Saudi Arabia: a cross-sectional study - Mukhtar, Mohamed A.; Abdelmajed, Ashwag H.; Alamin, Ahmed A.; Ali, Mohammed; Babikir, Marwa M.; Tifoor, Mosab; Elsheikh, Nihal E.; Omer, Ezaldeen H.; Mohammed, Nisreen G.; Abdelgadir, Sara M.; Ibrahim, Mohamed E.; Ali, Mozdaher G.; et al. (International Journal Of Community Medicine And Public Health, 2025)
Background: Gestational diabetes mellitus (GDM) is a common pregnancy complication associated with significant short- and long-term health risks for both mother and child. Understanding the local prevalence and associated risk factors is essential for improving antenatal care and long-term maternal health in Saudi Arabia. This study aimed to determine the prevalence of GDM among pregnant women and to assess its associated risk factors, management strategies, adherence levels, and postpartum outcomes. Methods: A cross-sectional study was conducted among 120 pregnant women attending antenatal clinics. Data were collected using structured interviews and medical records, focusing on demographics, obstetric history, GDM diagnosis, trimester of diagnosis, management modalities, treatment adherence, and postpartum follow-up including diabetes development. Statistical analysis was performed using chi-square tests to identify significant associations. Results: A total of 120 women participated in this study. The prevalence of GDM was 51.7%. The majority of cases were diagnosed in the first trimester (41.7%), followed by the second (30.8%) and third trimesters (27.5%). GDM was managed primarily through diet control (53.3%). A total of 71.7% reported treatment adherence, and 78.3% indicated adequate glycemic control and follow-up. Significant associations were found between GDM and employment status, BMI, and post-delivery diagnosis of diabetes. Postpartum, 21.7% were diagnosed with T2DM. Conclusions: This study reveals a high prevalence of GDM among pregnant women in Saudi Arabia. Despite good adherence and management rates, the transition to T2DM postpartum remains a concern. These findings highlight the importance of early screening, lifestyle interventions, and continuous postpartum monitoring to reduce GDM-related complications.